Diversity management and the role of leader - Ummeh Habiba Faria Benteh Rahman (Open Economics, 2019)
The paper's intention is to provide the correspondence of the globalization and the diversity in the management in this current trade era. The aim of the article is to understand the leader's role in diversity management which is rapidly changing the global trade market more clearly. Globalization has a very big influence on the diversity management these days, both directly and indirectly. This study is based on a systematic review of 14 journal articles presented on the concerned topic. It is divided into three main parts: the paper describes benefits of diversity management, leader's role and the challenges which leaders face while playing the role in the diverse management. In the review, it was found that "diversity" in the workplace is one of the most important factors to run the business or corporation smoothly and workplaces are truly benefitted by the management of the diversity. It works as an "aid to trade" in the performance of the workforce in the corporate culture. Next, we explained the challenges which leaders face and how to avoid those by taking initial steps. The paper ends up by providing discussions, limitations of the previous literature and some suggestions to the future researchers.
Keywords: 330; Challenges in Diversity Management; Diversity Management; Role of Leaders; Workplace Diversity